USULAN PENJADWALAN PRODUKSI YANG TERINTEGRASI DENGAN PENJADWALAN MAINTENANCE (STUDI KASUS PT. XYZ) - Hidayat, Trifenaus Prabu; Sutoto, Felix Eddy (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
PT XYZ is a company engaged in the automotive sector. Problems faced by companies today is the engine damage that often occurs during the production process therefore delaying the production process. Maintenance activities by the company is corrective maintenance, but there are preventive maintenance treatments which include cleaning and lubrication of machines carried out during holidays. Through already collected data it can be proposed for the company to have preventive maintenance with replacement and inspection engine components. Therefore, it is also necessary to take maintenance scheduling into the account of production scheduling. The focus of this research is the optimization of production scheduling in consideration with maintenance scheduling using makespan minimization criterias. The comparison of production scheduling that takes into account maintenance scheduling and maintenance scheduling with merging adjacent inspection and replacement timing is a difference of 0599% in January 2010, 0038% in May 2010 and 0221% in June 2010.